Pengaruh Due Profesional Care, Independensi dan Pengalaman Kerja Pada Kualitas Audit Dengan Reward Sebagai Pemoderasi - Krisna Naradipa, I Dewa Agung Gede; Supadmi, Ni Luh (E-Jurnal Akuntansi; Vol 29 No 1 (2019)DO - 10.24843/EJA.2019.v29.i01.p01, 2019)
Audit quality is very important, because high audit quality is expected to produce relevant and reliable financial statement information as the basis for decision making. The purpose of this study was to determine the effect of care due professional, independence and auditor work experience on audit quality with reward as moderating variables in KAP in Bali Province in 2018. The population of this study, all auditors working in KAP in Bali, amounting to 76 people . non probability sampling is a sample research method used, with data analysis techniques using Moderated Regression Analysis. The results of the analysis indicate that: care due professionals, independence, and work experience, statistically have a positive effect on audit quality. The results also show that the reward variable strengthens Due Professional Care relationship and work experience with audit quality, but the reward variable is not able to moderate the relationship of independence with audit quality. Keywords : Care Professional; Independence; Experience; Reward; Quality Audit.